Soil moisture characteristics of four artificial plant communities in aerial seeding afforestation area and their response to different levels of rainfall - Zhang, Tiejun; Liu, Yanping; Guo, Jianying; Tang, Guodong; Yang, Zhenqi (Frontiers in Forests and Global Change, 2025)
Studying the characteristics of soil moisture in afforestation area and its response to different grades of rainfall is helpful to quantitatively analyze the change law of soil moisture in afforestation area and provide theoretical basis for rational and efficient use of soil moisture. In this study, four artificial plant communities were selected, including Hedysarum scoparium community, Calligonum mongolicum community, H. scoparium- C. mongolicum community and C. mongolicum- H. scoparium community. The soil moisture content, soil moisture storage and their response characteristics to different grades of rainfall from June to October were compared and analyzed. The results showed that the SMC of H. scoparium- C. mongolicum community and C. mongolicum- H. scoparium community were lower than that of H. scoparium community and C. mongolicum community. The coefficient of variation of soil moisture content in C. mongolicum community was the largest, which was 22.7%, and the coefficient of variation of soil moisture content in H. scoparium-C. mongolicum community was the smallest, which was 19.4%. The recharge of rainfall to soil moisture storage of four artificial plant communities was different. The recharge of different grades of rainfall to soil moisture storage of C. mongolicum community and C. mongolicum-H. scoparium community was higher than that of H. scoparium community and H. scoparium-C. mongolicum community. In general, the utilization of soil moisture content in different soil layers by H. scoparium-C.mongolicum community is more balanced, and the soil moisture content in each soil layer is less affected by rainfall and has higher stability. Therefore, considering the configuration mode of H. scoparium- C. mongolicum community in the future aerial seeding afforestation process is conducive to the rational and efficient utilization of soil moisture in the afforestation area.